Attendance record of college activities (arca) with integration of scrutinization and report generator module / Mohd Fahmy Izwan Zulkhafri ... [et al.] - Zulkhafri, Mohd Fahmy Izwan; Jamaluddin, Muhammad Nabil Fikri; Jamil, Mohd Hairul Nazreen; Mohd Fauzi, Shukor Sanim; Razak, Tajul Rosli; Gining, Ray Adderley Jm; Mohd Zaki, Nurul Ain; Maskat, Ruhaila (2020)
Students’ attendance in all academic institutions are very important and cannot be overlooked because there are pre-determined criteria for attendance in class, college activities and examinations. Manual method of taking student attendance activity is not effective due to several challenges. Data collected through conventional method is difficult to manage, time-consuming to be scrutinized, and causes wastage of human and material resources. Therefore, aim of this project is to integrate a developed system, Attendance Record of College Activities (ARCA) with a scrutinization of college application and report generator modules. The project involved three main phases which are requirement identification, design and development, and testing phases in part of the research methodology. The study also involves usability and functionality testing by using unit test, script testing and distributed post-task questionnaires respectively to the college manager, college staff, staff resident college and to the students in UiTM Perlis branch. The results of usability testing show that most users satisfy with the integration of modules in ARCA system to full fill their day-to-day work. This shows the modules integration provide significant impact and present very promising results.